Without a map ; political tactics and economic reform in Russia - "Shleifer , Andrei" (Cambridge, 2000)
Recent commentators on Russia's economic reforms have almost uniformly declared them a disappointing and avoidable -- failure. In this book, two American scholars take a new and more balanced look at the country's attempts to build capitalism on the ruins of Soviet central planning. They show how and why the Russian reforms achieved remarkable breakthroughs in some areas but came undone in others. Unlike Eastern European countries such as Poland or the Czech Republic, to which it is often compared, Russia is a federal, ethnically diverse, industrial giant with an economy heavily oriented toward raw materials extraction. The political obstacles it faced in designing reforms were incomparably greater. Shleifer and Treisman tell how Russia's leaders, navigating in uncharted economic terrain, managed to find a path around some of these obstacles. In successful episodes, central reformers devised a strategy to win over some key opponents, while dividing and marginalizing others. Such political tactics made possible the rapid privatization of 14,000 state enterprises in 1992-1994 and the defeat of inflation in 1995. But failure to outmaneuver the new oligarchs and regional governors after 1996 undermined reformers' attempts to collect taxes and clean up the bureaucracy that has stifled business growth. Renewing a strain of analysis that runs from Machiavelli to Hirschman, the authors reach conclusions about political strategies that have important implications for other reformers. They draw on their extensive knowledge of the country and recent experience as advisors to Russian policymakers. Written in an accessible style, the book should appeal to economists, political scientists, policymakers, businesspeople, and all those interested in Russian politics or economics.
Keywords: "Russia,federation- politics and government-1991"